The relationship of acculturation to cardiovascular disease risk factors among U.S. South Asians: Findings from the MASALA study. (March 2020) - Al-Sofiani, Mohammed E.; Langan, Susan; Kanaya, Alka M.; Kandula, Namratha R.; Needham, Belinda L.; Kim, Catherine; Vaidya, Dhananjay; Golden, Sherita H.; Gudzune, Kimberly A.; Lee, Clare J.
Abstract: Aim: We investigated the association between acculturation strategies and cardiometabolic risk among South Asian (SA) immigrants in the US. Methods: In this cross-sectional analysis of data from 849 SA participants in the Mediators of Atherosclerosis in SAs Living in America (MASALA), we performed multidimensional measures of acculturation to categorize the participants into three acculturation classes: separation (preference for SA culture), assimilation (preference for US culture), and integration (similar preference for both cultures). Differences in glycemic indices, blood pressure, lipid parameters and body composition by acculturation strategy were examined. Results: Women in the integration class had the lowest prevalence of diabetes (16.4%), prediabetes (29.7%), fasting and 2-h glucose compared to women in the separation class with the highest prevalence of diabetes (29.3%), prediabetes (31.5%), fasting and 2-h glucose and 2-hr insulin (all p < 0.05 ). Women in the assimilation class had significantly lower triglycerides, BMI, and waist circumference and higher HDL compared to women in the separation class after adjusting for age, study site, and years in the US. After additionally accounting for socioeconomic/lifestyle factors, women in the assimilation class had significantly lower triglyceride and higher HDL levels compared to women in the separation class ( p < 0.01 ). There was no significant association between acculturation strategies and cardiometabolic risk in SA men. Conclusion: SA women who employed an assimilation or integration strategy had a more favorable cardiometabolic profile compared to women using a separation strategy. Future research should investigate the behavioral and psychosocial pathways linking acculturation strategies with cardiometabolic health to inform preventive interventions among SAs living in America.